2016
DOI: 10.4236/ojbm.2016.44064
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Review on Institutional Change and Entrepreneurship

Abstract: The literature argues that what is an institution, how institution changes, and the relationship between institutional change and entrepreneurship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…Aktivitas tersebut dapat saja melibatkan penerapan teknologi atau pendekatan baru dalam upaya menciptakan nilai sosial sehingga kewirausaahan sosial memainkan peran sebagai agen perubahan di sektor sosial dan terlibat dalam proses inovasi, adaptasi dan pembelajaran yang berkelanjutan (Certo & Miller, 2008) Dasar pemikiran penelitian ini adalah bahwa kewirausahaan sosial merupakan isu utama dalam pengentasan kemiskinan dan mampu meningkatkan kesejahteraan masyarakat, Sehingga pelaku kewirausahaan sosial disebut sebagai agen perubahan. Beberapa penelitian telah membahas peranan penting kewirausahaan sosial (Seda & Ismail, 2020) (Wang & Yee, 2023). Penelitian ini menunjukkan beberapa negara terutama negaranegara berkembang terus menerus gagal mengatasi perubahan sosial ekonomi yang berkembang di negaranya.…”
Section: Pendahuluanunclassified
“…Aktivitas tersebut dapat saja melibatkan penerapan teknologi atau pendekatan baru dalam upaya menciptakan nilai sosial sehingga kewirausaahan sosial memainkan peran sebagai agen perubahan di sektor sosial dan terlibat dalam proses inovasi, adaptasi dan pembelajaran yang berkelanjutan (Certo & Miller, 2008) Dasar pemikiran penelitian ini adalah bahwa kewirausahaan sosial merupakan isu utama dalam pengentasan kemiskinan dan mampu meningkatkan kesejahteraan masyarakat, Sehingga pelaku kewirausahaan sosial disebut sebagai agen perubahan. Beberapa penelitian telah membahas peranan penting kewirausahaan sosial (Seda & Ismail, 2020) (Wang & Yee, 2023). Penelitian ini menunjukkan beberapa negara terutama negaranegara berkembang terus menerus gagal mengatasi perubahan sosial ekonomi yang berkembang di negaranya.…”
Section: Pendahuluanunclassified
“…Audretsch, (2003) has also identified a number study that found a connection between the level more entrepreneurship tall with more unemployment low. Already is very common thing that objective education entrepreneurship is To add the number of businessmen new, (Linan, 2007;Veenswijk, 2012;Tao, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the study of the business process, research has revealed the importance of institutions in the development of the system because, according to Tao (2016), the economy deals with them. In this regard, there are two basic currents of institutional economic thinking, namely the Original Institutional Economics based on the tradition of Veblen, Ayres, Commons and Mitchell, and the New Institutional Economics, known as the North-Williamson School, which considers companies to be one of the most important institutions in the modern world (Parada 2003).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…He also clarifies that these institutions change from country to country. According to Tao (2016), institutions are broadly defined as lasting systems of established and incorporated social rules that structure social interactions. Language, money, law, weight and measuring systems, vehicle traffic rules, table manners, companies and other organizations are all institutions.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation